Impact Of Arabic Language Academies And Their Foundations On Community Service/ أثر مجامع اللغة العربية ومؤسساتها في خدمة المجتمع - Alsaud, Ali Ibrahim (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This research is a descriptive approach that studies the impact of linguistic academies and institutions concerned with the Arabic language on both the local and the Arab communities. The boundaries of the study are the linguistic academies in Saudi Arabia, Egypt, Iraq, Jordan, Algeria, Syria, and other linguistic institutions; it aims to monitor the goals of the academies and institutions and to show their relationship with society, in addition, to highlight the areas of cooperation between them, to present the areas in which community can be served, and to identify the core obstacles facing these academies and institutions in their linguistic mission. Therefore, the research answers an important question: Is there an impact of Arabic linguistic academies and institutions on the local and Arab community? The sample of study adopted by the research was all the Arab academies, the most prominent of which are the Iraqi, Syrian, Jordanian, Egyptian, Saudi, and Algerian Arabic language academies, by tracking their websites and printed books and collecting the topics they published, and have a direct relationship with the local and Arab community. The most important goals of these academies are to preserve the integrity of the Arabic language, to take care of new terms and Arabize them, to establish linguistic issues, to monitor the reality of the Arabic language, and to make linguistic dictionaries. One of the aspects of the relationship between the academies and the community is through carrying out linguistic projects, communicating with it, and holding courses and competitions for it. The research clarified the most significant obstacles that affect this relationship, the most important of which are low financial resources, the rarity of linguistic experts, and media weakness. The research concludes with the need to break the elite control of linguistic academies and institutions and to expand the integration of human potentials that serve the Arabic language so that there are multiple windows of influence and the need to involve segments of society in linguistic thinking, its problems, ways to solve it and to pay attention to computational, psychological, social, political linguistics, by offering courses, programs, and diplomas that assist national plans for human development.